Android-Based Educational Model Cross Puzzle to Improve Dental Health Behavior among Elementary Schools - Nurizza, Efa; Santoso, Bedjo; Rasipin, Rasipin; Marsum, Marsum; Wiyatini, Tri (Alta Dharma Publisher, 2022)
Background: Dental health problems in the intervention group primary school were dental caries at 81%, persistence at 32%, gingivitis at 35%, and dental health problems in the control group primary school namely dental caries at 86%, persistence at 36%, gingivitis 48%. Dental health problems in elementary school children are caused by low dental health maintenance behavior. The strategy to overcome this problem is by using an